Outcomes 60 years after surgical valvotomy for isolated congenital pulmonary valve stenosis. Issue 4 (1st February 2021) - Sekhon, Subhjit; Barger, Philip M.; Abarbanell, Aaron M.
Abstract: Congenital pulmonary valve stenosis (PVS) is a common congenital heart defect. In the infancy of cardiac surgery, open surgical valvotomy or closed surgical transventricular pulmonary valvotomy (Brock procedure) were the mainstays of therapy. We report the longest‐known published follow‐up of two women who as young children underwent pulmonary valvotomy for PVS and subsequent uncomplicated open pulmonary valve replacement over 60 years later.